An Asymmetry Field‐Effect Phototransistor for Solving Large Exciton Binding Energy of 2D TMDCs. Issue 7 (10th January 2022) - Ra, Hyun‐Soo; Ahn, Jongtae; Jang, Jisu; Kim, Tae Wook; Song, Seung Ho; Jeong, Min‐Hye; Lee, Sang‐Hyeon; Yoon, Taegeun; Yoon, Tea Woong; Kim, Seungsoo; Taniguch, Takashi; Watanabe, Kenji; et al.
Abstract: The probing of fundamental photophysics is a key prerequisite for the construction of diverse optoelectronic devices and circuits. To date, though, photocarrier dynamics in 2D materials remains unclear, plagued primarily by two issues: a large exciton binding energy, and the lack of a suitable system that enables the manipulation of excitons. Here, a WSe2 ‐based phototransistor with an asymmetric split‐gate configuration is demonstrated, which is named the "asymmetry field‐effect phototransistor" (AFEPT). This structure allows for the effective modulation of the electric‐field profile across the channel, thereby providing a standard device platform for exploring the photocarrier dynamics of the intrinsic WSe2 layer. By controlling the electric field, this work the spatial evolution of the photocurrent is observed, notably with a strong signal over the entire WSe2 channel. Using photocurrent and optical spectroscopy measurements, the physical origin of the novel photocurrent behavior is clarified and a room‐temperature exciton binding energy of 210 meV is determined with the device. In the phototransistor geometry, lateral p–n junctions serve as a simultaneous pathway for both photogenerated electrons and holes, reducing their recombination rate and thus enhancing photodetection. The study establishes a new device platform for both fundamental studies and technological applications. Abstract : An asymmetric split‐gate phototransistor configuration, called the "asymmetry field‐effect phototransistor" (AFEPT) is demonstrated. The structure allows for an effective modulation of the electric‐field profile throughout the channel, as well as enhanced photocarrier transport, thereby providing a new platform for improving optoelectronic properties and probing photocarrier dynamics in intrinsic 2D material layers.